Penyusunan Laporan Keuangan UMKM Berbasis Online dengan Aplikasi LAMIKRO - soraya, Soraya; Riyani, Yani; Mardiah, Kartawati; Andriana, Susan; Irawati, Rika; Rukmi, Murti Puspita; Cahyowati, Anik (Politeknik Negeri Madiun, 2020)
In the digital era as it is today, information technology has a significant impact on the process of accounting records in a company. However, the human resource factor is an obstacle for SMEs to develop and be able to compete with large companies. Moreover, if it is associated with the importance of presenting financial statements that are accountable and in accordance with standards, it requires MSMEs to be responsive to technological changes that occur. The existence of these demands, made the Ministry of Cooperatives and Small and Medium Enterprises (SMEs) in October 2017 launch an online-based application that is the Micro Business Accounting Report (Lamikro) application. The purpose of this Community Service activity is to provide knowledge about the preparation of financial statements with the application of Lamikro to MSMEs that are found in the Office of Cooperatives, Micro Business and Trade of Pontianak City. The participants who attended were 34 MSMEs. The methods applied are lecture, tutorial and discussion methods. Before giving a lecture, participants are given pre-test questions first. The pre-test results showed that 80% of participants did not understand the preparation of financial reports both manually and online. At the end of the activity a post test was conducted, which showed that 82.79% of participants had understood the preparation of financial reports both manually and online. This means, there is an increase in the knowledge and understanding of participants from before training and after training. Â Keywords: MSME, Financial Statements, Lamikro